Problems of Improving the Culture of Family Relations in Youth (Zien Journal of Social Sciences and Humanities, 2022)
In this article, issues such as the importance of strengthening family relations, family upbringing, development of society, family well-being, maturity and moral integrity of young people are researched as an important factor in the implementation of the goal.